How Much Cultural AssumptÄ±ons Matter In â€œCorporate ReputatÄ±on DÄ±mensÄ±onsâ€ of the FÄ±rms: A Study from TurkÄ±sh TelecommunÄ±catÄ±on Industry - KÄ±yat, Banu DayanÃ§; Ã‡alÄ±ÅŸkan, Sezer Cihan (Mediterranean Journal of Social Sciences, 2012)
The main purpose of this study is to examine the impact of cultural assumptions on corporate reputation perception of Turkishcitizens mainly in Turkish telecommunication industry. Today in the globalised markets, in which the life cycles of products becomesshorten and differentiation between products diminish, as a company to be preferred, the key of the success lies in intangible assests.â€œReputationâ€ is such an intangible and valuable asset which makes a company preferred by whole stakeholders and which creates acompetitive advantage for the companies. During the process of building of the reputation perception, cultural assumptions and values ofthe stakeholders are going to be influenced by national cultural values of the stakeholders (customers, suppliers, citizens, society,rivals..) Within the scope of this study impact of two cultural dimensions are tested namely: Individualism/ Collectivism and Masculinity/Feminity. According to study results, horizontal individualism and feminity are the dominant cultural assumption prevaling in Turkishtelecommunication sector in determining corporate reputation perception, whereas horizontal collectivist assumptions are the mostprevailing one in determining the sector free general perception of reputation quotient. The people who have horizontal collectivistcultural assumptions, give importance much more to the inner dynamics of the company (i.e, workplace environment, leadership andfinancial performance) in their perception of RQ (reputation quotient). This studyâ€™s theoretical contribution is the examination of effects ofcultural dimensions on corporate reputation perception of the companies in a comprehensive model; proposing new variables (affect ofcorporate reputation on employee attitudes and behaviors like organizational commitment, intention to turnover, job satisfaction,organizational citizenship behavior etc in terms of organizational behavior; and on customer satisfaction, brand loyalty and companyperformance as strategic management variables) in the model and filling this gap in the research.